2016
DOI: 10.1016/j.ijmst.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

A case study of multi-seam coal mine entry stability analysis with strength reduction method

Abstract: In this paper, the advantage of using numerical models with the strength reduction method (SRM) to evaluate entry stability in complex multiple-seam conditions is demonstrated. A coal mine under variable topography from the Central Appalachian region is used as a case study. At this mine, unexpected roof conditions were encountered during development below previously mined panels. Stress mapping and observation of ground conditions were used to quantify the success of entry support systems in three room-and-pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 2 publications
1
22
0
Order By: Relevance
“…It is widely used in civil and mining engineering applications (e.g. Tulu et al, 2016;Sears et al, 2018). Its application to geological systems across a range of scales can be found in the literature (e.g.…”
Section: Modelling Methodologymentioning
confidence: 99%
“…It is widely used in civil and mining engineering applications (e.g. Tulu et al, 2016;Sears et al, 2018). Its application to geological systems across a range of scales can be found in the literature (e.g.…”
Section: Modelling Methodologymentioning
confidence: 99%
“…This paper focuses on mining in the Kellioka Seam, located below workings in the Owl and Darby coal beds. The majority of the mining layout and geotechnical parameters for the study areas were published in previous papers [ 1 , 2 ]. Two particular parameters to be expanded upon in this paper are the multiple-seam mining geometry and the variable geology encountered in these four panels.…”
Section: Mining and Geotechnical Parametersmentioning
confidence: 99%
“…During an evaluation of unexpected conditions experienced at an eastern Kentucky room and pillar retreat mine that was conducted as part of a NIOSH research effort, it became evident that several factors associated with stress redistribution were involved. The initial efforts and results were published in the past two International Conference on Ground Control in Mining (ICGCM) proceedings by Tulu et al [ 1 , 2 ]. These two publications concluded that topographical changes and multiple-seam interactions were the cause of the unexpected conditions leading to the difficulties experienced in panels L6 and L4.…”
Section: Introductionmentioning
confidence: 99%
“…Coal is an unusual porous material, which has fissures, low intensity strength, heterogeneous texture, and permeability distinguishing it from regular porous materials [6,7]. Gas within the coal seam can strongly affect coal strength, deformation, and fracture propagation, and other mechanical properties [8][9][10]. In underground coal mines, gas is stored in a coal seam mainly in absorbed form or free state.…”
Section: Introductionmentioning
confidence: 99%